1977
DOI: 10.1021/bi00621a019
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of histones in avian erythroid cells

Abstract: The synthesis and enzymatic modifications of histones by phosphorylation, acetylation, and methylation during erythroid cell maturation have been studied. All newly synthesized histones, H1, H5, H2a, h2b, h3, and H4 undergo phosphorylation; histones H2a, H2b, H3, and H4, are acetylated and histones H3 and H4 are methylated. This type of histone metabolism is common to all dividing cells and therefore may be related to the assembly of histones into chromatin subunits. In the nondividing reticulocytes, the synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 27 publications
(24 reference statements)
3
35
0
Order By: Relevance
“…Recently, Sarg et al (29) found that H5 in mature chicken erythrocytes undergoes acetylation at the N terminus and that both unacetylated and acetylated forms are present. No other H1 subtypes in these cells are known to contain any modifications although some core histones were found to be acetylated (45). To our knowledge, the presence of eventual histone modifications in mature frog erythrocytes has not been investigated, but it seems unlikely that post-translational modifications are the reason for the large differences in linker histone affinity for chromatin found between chicken and frog erythrocytes.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, Sarg et al (29) found that H5 in mature chicken erythrocytes undergoes acetylation at the N terminus and that both unacetylated and acetylated forms are present. No other H1 subtypes in these cells are known to contain any modifications although some core histones were found to be acetylated (45). To our knowledge, the presence of eventual histone modifications in mature frog erythrocytes has not been investigated, but it seems unlikely that post-translational modifications are the reason for the large differences in linker histone affinity for chromatin found between chicken and frog erythrocytes.…”
Section: Discussionmentioning
confidence: 90%
“…Each of the lysine residues can accept up to three methyl groups forming mono-, di-, and trimethylated derivatives, thus adding a further potential complexity to the posttranslational status of histone H3 (12,13). The detailed biological role of mono-, di-, and trimethylation, however, is completely unknown to date.…”
mentioning
confidence: 99%
“…The histone H5 may be considered as an H1 variant emerging in the earliest forms of erythroid cells in connection with cell specialization in embryonic [3] and adult life [4]. As erythropoiesis proceeds, the early dividing cells differentiate into non-dividing reticulocytes and then into no longer transcribing mature erythrocytes.All the histones in normal dividing cells are synthesized at the time when DNA replication occurs, while histone H5 is the only one synthesized in the non-dividing reticulocytes [5,6]. During the terminal stages of erythrocyte differentiation the histone H5 accumulated up to a ratio of 3: l for H5/Hl in mature erythrocytes, accompanied by a transition to supercompaction of the chromatin and reduced transcriptional activity.…”
mentioning
confidence: 99%
“…All the histones in normal dividing cells are synthesized at the time when DNA replication occurs, while histone H5 is the only one synthesized in the non-dividing reticulocytes [5,6]. During the terminal stages of erythrocyte differentiation the histone H5 accumulated up to a ratio of 3: l for H5/Hl in mature erythrocytes, accompanied by a transition to supercompaction of the chromatin and reduced transcriptional activity.…”
mentioning
confidence: 99%